Violence in football stadiums in Ecuador: causes, manifestations, and prevention strategies (Revista científica Olimpia, 2026)
This study was developed in response to the need to evaluate the effectiveness of legislation and public policies in countering violence in Ecuadorian football stadiums, a prominent sport that faces high levels of aggression. Its objective was to analyze the normative consistency and practical implementation of these measures. To this end, a qualitative methodology was used, which included documentary review and content analysis of laws, regulations, and reported cases between 2018 and 2023, complemented by interviews with key stakeholders. The research obtained revealing results, showing that, although there is a specific regulatory framework, its implementation is irregular and limited by deficiencies in institutional coordination, lack of adequate training, and low community participation. Likewise, gaps were identified in the integration of preventive and educational strategies to promote a culture of respect. Consequently, the conclusions highlighted the urgency of strengthening regulatory and operational mechanisms, for which a comprehensive model was proposed that coordinates policies, staff training, monitoring, and the active participation of sports communities. This contribution is relevant for the legal, social, and sports sectors of the country, emphasizing the importance of ensuring safety and the respect of human rights at football events.
Keywords: Sports culture; ecuadorian legislation; public policies; violence prevention; safety in sporting events